The Six-Minute Walk as A Safety Exercise in Improving the Health-Related Quality of Life Among Heart Failure Patients: A Preliminary Research - Nurhayati Nurhayati; Andri Kusuma Wijaya; Nova Yustisia; Tuti Anggraini (KHD Production, 2023)
The prevalence of heart failure patients is steadily increasing worldwide. The quality of life among them was also shown to be decreasing day by day. Inadequate health-related quality of life in heart failure patients leads to an increase in mortality rate. Thus, effective management of heart failure patients is essential. The present study was to examine the intervention based on the six-minute walk test to improve health-related quality of life for patients with heart failure. A quasi-experimental study was conducted in the cardiovascular center of the acute care setting. The Six-minute Walk Test (6MWT), in accordance with the American Thoracic Society guideline, was implemented as the intervention procedure. The Minnesota Living with Heart Failure (MLWHF) was used to measure the health-related quality of life of patients. Fifteen heart failure patients enrolled in the study for a month; 73.3% were male with a mean age of 57.47 (SD 14.32). Overall, the health-related quality of life in heart failure patients was poor at the baseline of the study, then their quality of life significantly increased to good quality after implementing the 6MWT. An improvement in the functional performance was also found among them. This study indicates that the 6MWT was suitable, safe, and simply performed in heart failure patients, which can effectively improve the health-related quality of life of patients with heart failure.